2016
DOI: 10.1111/1365-2664.12760
|View full text |Cite
|
Sign up to set email alerts
|

Modelling flight heights of lesser black‐backed gulls and great skuas from GPS: a Bayesian approach

Abstract: 1.Wind energy generation is increasing globally, and associated environmental impacts must be considered. The risk of seabirds colliding with offshore wind turbines is influenced by flight height, and flight height data usually come from observers on boats, making estimates in daylight in fine weather. GPS tracking provides an alternative and generates flight height information in a range of conditions, but the raw data have associated error. 2. Here, we present a novel analytical solution for accommodating GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 30 publications
3
47
0
1
Order By: Relevance
“…There seems to be a general consensus that flapping flight of seabirds at sea, though not necessarily during migration, occurs at relatively low flight altitudes <100 m (Garthe and Hüppop 2004; Ross-Smith et al 2016). Within this relatively narrow altitude band, studies have shown that as expected from optimal migration theory seabirds as well as waterbirds fly at higher altitudes with supporting winds and lower altitudes with opposing winds (Krüger and Garthe 2001; Kahlert et al 2012; McLaren et al 2016) with waterbirds also reducing their flight altitude with increasing wind speed (Kahlert et al 2012).…”
Section: Individual Responsementioning
confidence: 99%
“…There seems to be a general consensus that flapping flight of seabirds at sea, though not necessarily during migration, occurs at relatively low flight altitudes <100 m (Garthe and Hüppop 2004; Ross-Smith et al 2016). Within this relatively narrow altitude band, studies have shown that as expected from optimal migration theory seabirds as well as waterbirds fly at higher altitudes with supporting winds and lower altitudes with opposing winds (Krüger and Garthe 2001; Kahlert et al 2012; McLaren et al 2016) with waterbirds also reducing their flight altitude with increasing wind speed (Kahlert et al 2012).…”
Section: Individual Responsementioning
confidence: 99%
“…Beyond energetics, characterising behavioural states in flying animals is particularly important to evaluate their susceptibility to human activities, informing effective planning and management (Katzner, Brandes et al., ; Péron et al., ; Ross‐Smith et al., ). For example, specific behavioural states, due to their horizontal and vertical characteristics, may put birds at higher risk of collision with turbines (Ross‐Smith et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ross‐Smith et al. () incorporated DOP as a linear effect into state‐space models showing that variation in DOP was strongly related to variation in flight altitude error. That error is also relevant when considering Péron et al.…”
Section: Technical Assumptionsmentioning
confidence: 99%
“…Finally, Ross‐Smith et al. () developed similar models that incorporated negative observations, but that ensured that all estimated true altitude values were above sea level (ASL; positive altitudes). Although the incorporation of flight altitude values into state‐space models is more complex than the use of a threshold, such models have their own weaknesses that may limit their utility and may affect ecological inference (Auger‐Méthé et al., ).…”
Section: Technical Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation